Ultrawideband radar : applications and design - Taylor, James D., 1941- (Boca Raton, FL : Taylor & Francis, 2012)
"This book outlines the latest advances in the theory, design, and implementation of ultrawideband (UWB) radar technology, which shows promise for use in diverse applications ranging from toilet flushing sensors and cancer detection equipment to radar sensors that could be used in homes, public places, cars, hospitals, and aircraft. Detailing their potential for use in medicine, security, and other key areas, the book covers topics including the technology's history and government regulation internationally. It also discusses propagation theory and examples of precision ranging as applied to material penetration, imaging, and additional medical applications"--
Introduction to Ultrawideband Radar Applications and Design / J.D. Taylor -- Development of Ultrawideband Communications Systems and Radar Systems / T.W. Barrett -- Signal Waveform Variations in Ultrawideband Wireless Systems: Causes and Aftereffects / I.Y. Immoreev -- American and European Regulations on Ultrawideband Systems / J.D. Taylor -- Principles of Materials-Penetrating Ultrawideband Radar Systems / J.D. Taylor -- Ultrawideband and Random Signal / Radar, H. Sun -- Automatic Measurement of Ground Permittivity and Automatic Detection of Object Location with GPR Images Containing a Response from a Local Object / M.M. Golovko and G.P. Pochanin -- UWB Pulse Backscattering from Objects Located near Uniform Half-Space / O.I. Sukharevsky, S.A. Gorelyshev, and V.A. Vasilets -- Medical Applications of Ultrawideband Radar /J.D. Taylor -- Large Current Radiators: Problems, Analysis, and Design / G.P. Pochanin and S.A. Masalov -- Novelda Nanoscale Impulse Radar / J.D. Taylor and D.T. Wisland -- Principles and Methods of Material-Penetrating UWB Radar Imagery / A. Boryssenko and E. Boryssenko -- Holographic Subsurface Radar Technology and Applications / S.I. Ivashov, L. Capineri, and T.D. Bechtel -- Xaver Through-Wall UWB Radar Design Study / J.D. Taylor, E. Hochdorf, J. Oaknin, R. Daisy, and A. Beeri -- The Camero, Inc., Radar Signal Acquisition System for Signal-to-Noise Improvement / J.D. Taylor, E. Hochdorf, A. Beeri, and R. Daisy -- The Camero, Inc., Time Delay Calibration System for Range Cell Synchronization / J.D. Taylor, E. Hochdorf, and N. Shani -- The Camero, Inc., UWB Radar for Concealed Weapons Detection / J.D. Taylor and E. Hochdorf
Includes bibliographical references and index.
Keywords: Ultra-wideband radar